2016
DOI: 10.1111/nph.14155
|View full text |Cite
|
Sign up to set email alerts
|

Novel allelic variants in ACD6 cause hybrid necrosis in local collection of Arabidopsis thaliana

Abstract: Hybrid necrosis is a common type of hybrid incompatibility in plants. This phenomenon is caused by deleterious epistatic interactions, resulting in spontaneous activation of plant defenses associated with leaf necrosis, stunted growth and reduced fertility in hybrids. Specific combinations of alleles of ACCELERATED CELL DEATH 6 (ACD6) have been shown to be a common cause of hybrid necrosis in Arabidopsis thaliana. Increased ACD6 activity confers broad-spectrum resistance against biotrophic pathogens but reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 66 publications
2
48
0
Order By: Relevance
“…Fifteen individual plants collected from Lövvik (Lov), Northern Sweden in year 2015 (Plotner et al, ), and 15 individual plants from Altenriet (Alt), Southern Germany in 2013 (Swiadek et al, ), were used in this study. In all conditions, soil contained 50% (v/v) fine white peat (Gramoflor GmbH) mixed with 30% (v/v) fine and 25% (v/v) coarse‐grained vermiculite peat (Fitz Kausek GmbH & Co).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen individual plants collected from Lövvik (Lov), Northern Sweden in year 2015 (Plotner et al, ), and 15 individual plants from Altenriet (Alt), Southern Germany in 2013 (Swiadek et al, ), were used in this study. In all conditions, soil contained 50% (v/v) fine white peat (Gramoflor GmbH) mixed with 30% (v/v) fine and 25% (v/v) coarse‐grained vermiculite peat (Fitz Kausek GmbH & Co).…”
Section: Methodsmentioning
confidence: 99%
“…To test the hypothesis, we analyzed plasticity to N availability in 65 primary metabolites as well as growth and fitness traits in two A. thaliana populations, one collected from Southern Germany and the other from Northern Sweden. These populations originate from different growth habitats and differ genetically (Plotner et al, ; Swiadek et al, ). Interestingly, we found that glutamine, an amino acid central to the assimilation of N, exhibited the highest plasticity in both populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the most severe cases of F 1 hybrid necrosis are lethal, the milder cases are partially fertile or have phenotypes that become visible only in the F 2 or later generations. All cases of hybrid necrosis show phenotypic characteristics typical of the defense response to pathogens in plants (Bomblies et al ., ; Alcázar et al ., , , ; Chae et al ., ; Todesco et al ., ; Swiadek et al ., ). The first causal gene pair underlying hybrid necrosis was identified from A. thaliana (Bomblies et al ., ).…”
Section: Hybrid Incompatibilities Caused By Interactions Between Genementioning
confidence: 97%
“…In contrast to the NLR s, where phenotypes result from an interaction between two or three different genes, interactions between different allelic variants of ACD6 can activate autoimmune responses in F 1 hybrids of A. thaliana (Todesco et al ., ; Swiadek et al ., ). Furthermore, interactions of different ACD6 alleles have been shown to cause different severity of symptoms in A. thaliana hybrids (Todesco et al ., ; Swiadek et al ., ). Although showing reduced fitness, these hybrids also display an increased disease resistance in comparison with their parents (Todesco et al ., ).…”
Section: Hybrid Incompatibilities Caused By Interactions Between Genementioning
confidence: 97%
See 1 more Smart Citation